Izglītības vides iespējas labizjūtas veicināšanā x sākumskolas 4. un 5. klasēs - Tilaka, Indra (Latvijas Universitāte, 2022)
Indras Tilakas diplomdarba “Izglītības vides iespējas labizjūtas veicināšanā X sākumskolas 4. un 5. klasēs” mērķis ir izpētīt labizjūtas jēdziena būtību un izglītības vides iespējas labizjūtas veicināšanā 4. un 5. klasēs pārejas posmā no sākumskolas uz pamatskolas mācību procesu. Teorētiskajā daļā analizēts labizjūtas jēdziens, tā koncepcijas izglītības aspektā, raksturotas izglītības fiziskās un psiholoģiskās vides iespējas labizjūtas veidošanās procesā un pedagogu darbība skolēnu labizjūtas veicināšanā, izmantojot pozitīvās pedagoģijas pieeju. Pētījuma daļā veikts empīrisks pētījums par skolotāju iespējām skolēnu emocionālo un mācību grūtību novēršanā labizjūtas veidošanās sekmēšanai un X sākumskolas 4.-5.klašu skolēnu labizjūtas izpēte. Praktiskajā daļā izstrādāta un realizēta sociālpedagoģiskās darbības programma labizjūtas veicināšanai X sākumskolas 4.un 5. klasēs.

The aim of graduation paper “Opportunities of the educational environment in promoting well-being in primary school X grades 4 and 5 ” written by Indra Tilaka is to explore the idea of the concept of wellbeing and the promotion of the educational environment in classes 4 and 5 as well as the transition from primary to upper-primary school. The theoretical part analyses the concept of well-being, its concepts in terms of education, describes the physical and psychological potential of education in the development of well-being and the role of educators in promoting the wellbeing of pupils through the positive approach of pedagogy. The practical part contains an empirical study on the possibilities of teachers in tackling the emotional and learning difficulties of pupils in order to contribute to the development of well-being and the study the well-being of pupils in classes 4 and 5 in primary school X. A social pedagogical action programme for promoting well-being in classes 4 and 5 has been developed and implemented in the practical part of this paper. Key words: educational environment, inclusive education, well-being, pupils, teachers, educators, positive pedagogy, teens, social teaching.
Opportunities Of The Educational Environment In Promoting Well-Being In Primary School Grades 4 And 5
Keywords: Pedagoģija; izglītības vide; iekļaujošā izglītība; labizjūta; pedagogi; pozitīvā pedagoģija